2017
DOI: 10.1037/dev0000345
|View full text |Cite
|
Sign up to set email alerts
|

An eye tracking investigation of attentional biases towards affect in young children.

Abstract: This study examines attentional biases in the presence of angry, happy and neutral faces using a modified eye tracking version of the dot probe task (DPT). Participants were 111 young children between 9 and 48 months. Children passively viewed an affective attention bias task that consisted of a face pairing (neutral paired with either neutral, angry or happy) for 500 ms that was followed by a 1,500-ms asterisk probe on 1 side of the screen. Congruent trials were trials in which the probe appeared on the same … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
56
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 40 publications
(68 citation statements)
references
References 40 publications
(63 reference statements)
8
56
4
Order By: Relevance
“…Previous work using traditional means across conditions did not find a relation between dwell time (to 500 ms face presentation) and a bias score (incongruent minus congruent) calculated from fixation latencies (Burris et al, in press). In contrast, our within-trial analysis found an interaction between age, dwell time to angry faces, and negative affect in predicting latency to probes.…”
Section: Discussionmentioning
confidence: 82%
See 3 more Smart Citations
“…Previous work using traditional means across conditions did not find a relation between dwell time (to 500 ms face presentation) and a bias score (incongruent minus congruent) calculated from fixation latencies (Burris et al, in press). In contrast, our within-trial analysis found an interaction between age, dwell time to angry faces, and negative affect in predicting latency to probes.…”
Section: Discussionmentioning
confidence: 82%
“…We did not find systematic sex-linked findings with our current sample and analytic strategy. It may be that larger samples, with alternate variables of interest (Burris et al, in press) or more fear-specific stimuli (e.g., spiders), are needed to reveal any emergent differences.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, a related study found an age‐related increase in probe fixation latency after infants fixated face pairs containing an emotional face, but not after trials with nonsocial threats (e.g., snakes) (LoBue, Buss, Taber‐Thomas, & Pérez‐Edgar, ). However, other cross‐sectional eye‐tracking studies with infants have not found significant age effects for affect‐biased attention (Burris et al, , 9‐ to 48‐month‐olds; Morales et al, , 4‐ to 24‐month‐olds).…”
Section: Introductionmentioning
confidence: 89%